PERANAN AUDITOR INTERNAL DALAM MENCEGAH FRAUD LAPORAN KEUANGAN: STUDI TEORI FRAUD HEKSAGON - Sudadi, Bhanu Sahitya; Achmad, Tarmizi (Diponegoro Journal of Accounting, 2024)
This research is intended to examine the influence of hexagon fraud theory factors on detecting financial statements fraud and the internal auditor’s influence on the relationship between fraud factors and financial statement fraud. This research was conducted on Property and real Estate companies from 2015 –to 2019. Independent variables according to fraud hexagon theory are proxied by financial stabillity, change of director, Whistleblowing System , Ineffective monitoring, and change of public accounting firm, executive compensation in the annual report. The dependent variable in this research is financial statements fraud that is proxied by Beneish M score and moderating variable is the number of company’s internal auditor.The population in this research are property and real estate companies listed on the Indonesian Stock Exchange (IDX) from 2015 to 2019. This research obtained samples using the purposive sampling technique and resulted in 109 years of observations out of 24 companies that matched the criteria. Logistic regression analysis is used in order to obtain results.Research results found that finansial stability, change in director , whistleblowing system, and change of public accounting firm able to impact on finansial statment fraud. Internal auditor doesn’t have any moderating impact on variables in this research.